Public Relations Roles Building School Image Through Islamic Character Programs: Peran Humas dalam Membangun Citra Sekolah Melalui Program Karakter Islami - Ninda Anayarahma; Ainur Rochmaniah (Academia Open, 2025)
General Background: Institutional image is essential for sustaining public trust and competitiveness in educational institutions through strategic communication management. Specific Background: SMP Muhammadiyah 1 Sidoarjo implements Islamic character development programs supported by public relations activities such as Ismuba For Student and religious-based student programs. Knowledge Gap: Studies commonly examine institutional reputation and character education separately, while limited research analyzes public relations roles in building school image through Islamic character strengthening in Islamic private schools. Aims: This study analyzes public relations roles in shaping school image through Islamic character development programs at SMP Muhammadiyah 1 Sidoarjo. Results: Public relations perform four main roles, namely communicator, relationship builder, management supporter, and institutional image builder, through dissemination of Islamic values, stakeholder relationship management, cross-divisional coordination, and publication of school achievements and religious activities. The programs are associated with student character formation, academic and non-academic achievements, and increased student enrollment. Novelty: This study integrates public relations functional roles with Islamic character education as a framework for institutional reputation development. Implications: The findings provide practical references for Islamic educational institutions in designing communication strategies based on character education and stakeholder engagement to strengthen institutional positioning. Highlights: Communication Channels Systematically Disseminate Religious Value Activities to Internal and External Stakeholders. Stakeholder Collaboration Programs Strengthen Parental and Community Participation in Student Development. Integrated Coordination Across School Divisions Supports Consistent Institutional Positioning. Keywords: Public Relations Strategy, Institutional Reputation, Islamic Education, Character Development, Stakeholder Communication